Clinical lymph node staging in colorectal cancer; a flip of the coin?. Issue 8 (August 2018) - Brouwer, Nelleke P.M.; Stijns, Rutger C.H.; Lemmens, Valery E.P.P.; Nagtegaal, Iris D.; Beets-Tan, Regina G.H.; Fütterer, Jurgen J.; Tanis, Pieter J.; Verhoeven, Rob H.A.; de Wilt, Johannes H.W.
Abstract: Background: This study aims to provide insight in the quality of current daily practice in clinical lymph node staging in colorectal cancer (CRC) in the Netherlands. Methods: Data of the nationwide population-based Netherlands Cancer Registry between 2003 and 2014 were used to analyze lymph node staging for cM0 CRC patients. Accuracy of clinical lymph node staging was calculated for the period 2011–2014. Analyses were performed for patients without preoperative treatment or treated with short-course radiotherapy (SCRT) followed by resection. Results: 100, 211 patients were included for analysis. The proportion clinically positive lymph nodes increased significantly between 2003 and 2014 (6%–22% for colon cancer; 7%–53% for rectal cancer). The proportion histological positive lymph nodes remained stable (±35% colon, ±33% rectum). Data from 2011 to 2014 yielded a sensitivity, specificity, positive and negative predictive value of 41%, 84%, 59% and 71% for colon cancer, respectively (n = 21, 629). This was 38%, 87%, 56%, 76% for rectal cancer without SCRT, (n = 2178) and 56%, 67%, 47% and 75% for rectal cancer with SCRT (n = 3401), respectively. Conclusion: Accuracy of clinical lymph node staging in colorectal cancer patients is about as accurate as flipping a coin. This may lead to overtreatment of rectal cancer patients. Acceptable specificity and NPV limit the risk of undertreatment.